CHARACTERISTICS OF ANDRIC’S POETRY FROM THE EARLY PERIOD - Šimun Musa (Hum, 2012)
With poems written in verse and prose in the early period, starting from the first poem “At Twilight”, (1911) to Ex Ponto (1918) and Unrest, (1920), his books of lyrics in prose, Andric tackled almost all styles before the First World War, in the war and post-war period but he was not seized by any school completely: there is influence of impressionistic, especially Matos’s “Grič school” or Parnassian-symbolist influence, then influences of neosymbolism, simultaneism and especially expressionistic poetics.